The theory of the numerical-analytic method: Achievements and new trends of development. IV - Ronto, M. I.; Samoilenko, A. M.; Trofimchuk, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We analyze the application of the numerical-analytic method proposed by Samoilenko in 1965 to autonomous systems of differential equations and impulsive equations.